Impact of transmitter positioning uncertainty on RSS-based visible light positioning accuracy - Chaudhary, Neha (2021)
This paper presents simulation-based results of the impact of transmitter (Tx) position uncertainty on the accuracy of the received signal strength (RSS)-based visible light positioning (VLP) system considering multipath reflections. RSS-based algorithms are constrained by several factors, most notably due to multipath channel characteristics and set-up uncertainties. A study on the impact of Tx uncertainties on positioning error performance is described. Simulation results show that, positioning accuracy can be severely compromised for positioning systems with a small number of Txs. We also show that higher lighting uniformity does not necessarily imply improved positioning performance. Furthermore, the error dependence on Tx’s position uncertainty reduces with increasing the number of Txs.